Preparation method and application of Co / Pd bimetallic catalyst derived from bimetallic porphyrin-doped MOFs
Through the in-situ integrated synthesis of MOFs-derived Co/Pd bimetallic catalysts by pre-restricted bimetallic strategy, the problem of complex and uneven preparation of active metals in the prior art is solved, and the high-efficiency hydrogen evolution performance and stability of the catalyst is achieved.
Patent Information
- Application Number
- CN202411478380.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing electrocatalytic hydrogen evolution catalysts are complex in preparation, and the introduction of active metals is uneven, resulting in insufficient catalytic activity and stability.
The pre-constrained bimetallic strategy is adopted, and CoTCPP and PdTCPP are used as structural guides to synthesize in situ MOFs-derived Co/Pd bimetallic catalysts, and the spatial isolation and uniform distribution of bimetallic through the metal organic framework formed by metal ligands is achieved.
The preparation process of the catalyst is simplified, the uniform distribution of Co/Pd metal nanoparticles is achieved, the electron synergy between non-precious metal Co and precious metal Pd is promoted, and the hydrogen evolution catalytic performance and stability of the catalyst is significantly improved.
Smart Images

Figure CN119243244B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalytic hydrogen evolution, and specifically relates to a preparation method and application of a Co / Pd bimetallic catalyst derived from bimetallic porphyrin-doped MOFs. Background Art
[0002] As traditional fossil fuels are gradually depleted and the demand for energy continues to grow, hydrogen energy has become a recognized green energy source. A sustainable and promising hydrogen production route, electrocatalytic water splitting, can be powered by excess electricity generated by renewable energy and is a beneficial tool for protecting the sustainable development of mankind.
[0003] Metal-organic framework (MOFs) materials are a new generation of precursor / template materials with unique advantages in material preparation. Catalysts designed based on MOFs are widely used. Researchers have taken effective measures to spatially isolate and restrict the migration of metal atoms through coordination species such as nitrogen (N), phosphorus (P), and sulfur (S), which can maximize the exposure of metal active sites and provide a stable chemical environment. In addition, by further regulating the precious metal and non-precious metal components to optimize the electronic structure of the catalyst, the catalytic activity and stability can be significantly improved. In CN116752185A, this research team used MOFs as the skeleton, first anchored Co atoms and porphyrin organic ligands with metal centers in the metal organic framework, and then potassium chloroplatinate was impregnated in the metal organic framework. After calcination, a carbon-based electrocatalyst containing pt and Co was prepared. This method can fully expose the Co single atom sites in the material and form a special composite structure of single-atom anchored nanoparticles. This material is suitable for electrocatalytic hydrogen evolution research under acidic conditions and has excellent hydrogen evolution effect and stability. However, the preparation method of the above-mentioned catalyst is relatively complicated. The active metal needs two steps to be introduced into the catalyst. After the pt metal is introduced by the impregnation reduction method, the binding force between the pt metal and the nitrogen-containing carbon material is relatively poor, resulting in insufficient stability. In addition, the impregnation reduction method has the problem of uneven dispersion of the pt metal and certain agglomeration, resulting in the catalytic activity to be improved.
[0004] In view of the above problems, the present invention proposes a "pre-constrained bimetallic" strategy, using CoTCPP and PdTCPP with unique porphyrin ring structures as structure-directing agents, in situ integrated synthesis of CoTCPP and PdTCPP-doped MOFs-derived Co / Pd bimetallic catalysts, and using metal organic framework materials formed by metal ligands to achieve spatial isolation of the bimetallics. The doped MOFs are subjected to high-temperature pyrolysis, and the metal nanoparticles Co / Pd are firmly anchored on the nitrogen-doped carbon skeleton substrate to form a close interface connection. In addition, the nitrogen-doped carbon skeleton is used to achieve uniform distribution of Co / Pd metal nanoparticles, promote the electronic synergistic effect of non-precious metal Co and precious metal Pd, thereby improving the hydrogen evolution catalytic performance of the Co / Pd bimetallic catalyst. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation method and application of a Co / Pd bimetallic catalyst derived from a bimetallic porphyrin-doped MOFs. The preparation process of the catalyst of the present invention is simple, and the synthesized catalyst Co / Pd bimetallic nanoparticles can be firmly anchored in a nitrogen-doped carbon skeleton substrate. The uniform distribution of the Co / Pd bimetallic nanoparticles promotes the electronic synergistic effect of the non-precious metal Co and the precious metal Pd, thereby improving the hydrogen evolution catalytic performance of the Co / Pd bimetallic catalyst.
[0006] The first aspect of the present invention provides a method for preparing a Co / Pd bimetallic catalyst derived from bimetallic porphyrin-doped MOFs.
[0007] The second aspect of the present invention provides a Co / Pd bimetallic catalyst derived from a bimetallic porphyrin-doped MOFs, which is specifically obtained by the preparation method of the present invention.
[0008] The third aspect of the present invention provides a use of a Co / Pd bimetallic catalyst derived from a bimetallic porphyrin-doped MOFs, specifically applying the catalyst to electrocatalytic hydrogen evolution.
[0009] The specific technical solutions are as follows:
[0010] The present invention provides a method for preparing a Co / Pd bimetallic catalyst derived from a bimetallic porphyrin-doped MOFs, the preparation method comprising the following steps:
[0011] 1) Add a certain amount of ZrCl 4 、BDC-NH 2 , benzoic acid, CoTCPP and PdTCPP are dissolved in DMF, ultrasonically dissolved and then transferred to a high-pressure reactor for reaction at 100°C-150°C for 16-36h.
[0012] 2) Cooling the solution after the reaction in step 1), recovering the solid product by centrifugation, repeatedly washing with ethanol, and then drying under vacuum to obtain Co / Pd-UiO-66-NH 2 Electrocatalyst.
[0013] 3) Co / Pd-UiO-66-NH 2 Place in a tube furnace and heat under N 2 Calcination under atmosphere to obtain Co / Pd-ZrO 2 -NC.
[0014] 4) Co / Pd-ZrO 2 -NC is added to HF aqueous solution, stirred continuously for 1-5h, washed several times with methanol aqueous solution, and dried under vacuum at 100°C for 2h to obtain Co / Pd-NC, which is a Co / Pd bimetallic catalyst.
[0015] Preferably, in the above step 1), the ZrCl 4 、BDC-NH 2 The mass ratio of benzoic acid, CoTCPP and PdTCPP is 9:4.5:100:1-3:1-3, preferably 9:4.5:100:1:1.
[0016] Further preferably, in the above step 1), ZrCl 4 、BDC-NH 2 The amounts of benzoic acid, CoTCPP and PdTCPP were 180 mg, 90 mg, 2000 mg, 20 mg and 20 mg respectively.
[0017] Further preferably, the mass usage ratio of CoTCPP to PdTCPP is 1-3:1-3.
[0018] The amount of metal organic ligands used will affect the performance of the catalyst. It is further preferred that the best catalytic performance can be obtained when the mass dosage ratio of CoTCPP and PdTCPP is 1:1. The amount of CoTCPP and PdTCPP used directly determines the content of Co and Pd in the catalyst. These two metals play a key catalytic role in the catalyst, and changes in their content will directly affect the number and distribution of active sites of the catalyst; the appropriate amount of CoTCPP and PdTCPP can promote the close combination of Co and Pd, thereby improving the mutual synergy and making the catalyst have better stability and catalytic performance. The synergistic effect of Co and Pd can also improve the selectivity of the catalyst, making the catalytic reaction more efficient and controllable. The appropriate amount of CoTCPP and PdTCPP can improve the stability of the catalyst, making it less likely to deactivate or degrade during use; because the appropriate amount of metal content and metal coordination will change the electronic structure of the metal, and by annealing or chemically encapsulating metal nanoparticles and loading them on a nitrogen-doped carbon skeleton substrate, it can not only inhibit the aggregation of the metal and achieve the exposure of highly active sites, but also promote the transfer of mass and charge. In addition, it may also produce a strong metal-support interaction (MSI) between the metal particles and the carrier, further improving the overall catalytic activity and stability.
[0019] Preferably, in the above step 1), the reaction temperature of the high-pressure reactor is 130° C. and the reaction time is 24 hours. The reaction temperature and time will affect the growth of the crystal. Too high or too low a temperature will result in a bad crystal form and affect the synthesized material to fail to achieve the desired processing efficiency.
[0020] Preferably, the vacuum drying temperature in the above step 2) is 60°C. Both temperature and pressure will affect the efficiency of vacuum drying. The lower the pressure, the more conducive it is to vaporize water at a lower temperature. However, too high a vacuum degree is not conducive to heat conduction and will affect the heating effect of the material.
[0021] Further, preferably, in the above step 3) N 2 The conditions for calcination in atmosphere are heating to 800℃ at a heating rate of 5℃ / min and maintaining for 2h. Heating at a heating rate of 5℃ / min can ensure that the thermal stress of the catalyst during the heating process is controlled. Too fast a heating rate may cause greater thermal stress inside the catalyst, causing structural damage or performance degradation; a moderate heating rate helps the organic matter and metal ions inside the catalyst to react uniformly during the heating process; at high temperatures, the metal ions in CoTCPP and PdTCPP can be reduced to metal atoms, and the two active metals can be evenly dispersed on the nitrogen-doped carbon skeleton substrate, which helps to form Co / Pd nanoparticles with excellent catalytic performance.
[0022] Preferably, the HF solution in step 4) is a 15 ml aqueous solution containing 0.1 mol HF, and the stirring time in the HF solution is 2 h. The main function of the HF solution is to etch away the ZrO in the MOF-derived material. 2 This step is key to releasing the Co / Pd bimetallic nanoparticles loaded on the support, allowing these nanoparticles to participate in the catalytic reaction more directly.
[0023] Preferably, the aqueous solution of methanol in the above step 4) is a mixed solution of methanol and water in a volume ratio of 1:4.
[0024] The second aspect of the present invention provides a Co / Pd bimetallic catalyst derived from a bimetallic porphyrin-doped MOFs prepared by the preparation method described in any one of claims 1 to 8, wherein the Co / Pd bimetallic nanoparticles are fixed and dispersed in a nitrogen-doped carbon skeleton.
[0025] The third aspect of the present invention provides a use of a Co / Pd bimetallic catalyst, wherein the Co / Pd bimetallic catalyst is used for electrocatalytic hydrogen evolution. The bimetallic catalyst synthesized by the present invention is suitable for electrocatalytic hydrogen evolution research under acidic and alkaline conditions, and exhibits excellent hydrogen evolution effect and stability. In acidic and alkaline solutions, the catalyst Co prepared by the present invention 20 Pd 20 -NC at 10mA·cm -2 The current density provided a very small overpotential of 23mV and 52mV respectively.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The present invention proposes a "pre-constrained bimetallic" strategy, using CoTCPP and PdTCPP with unique porphyrin ring structures as structure-directing agents, in situ integrated synthesis of CoTCPP and PdTCPP-doped MOFs-derived Co / Pd bimetallic catalysts, and using metal organic framework materials formed by metal ligands to achieve spatial isolation of the bimetallics. The doped MOFs are subjected to high-temperature pyrolysis, and the metal nanoparticles Co / Pd are firmly anchored on the nitrogen-doped C substrate to form a tight interface connection. In addition, the nitrogen-doped carbon skeleton is used to achieve uniform distribution of Co / Pd metal nanoparticles, promote the electronic synergistic effect of non-precious metal Co and precious metal Pd, thereby improving the hydrogen evolution catalytic performance of the Co / Pd bimetallic catalyst. The Co / Pd bimetallic catalyst obtained by the preparation method of the present invention has excellent hydrogen evolution performance in the field of electrocatalytic hydrogen evolution.
[0028] (2) The preparation method provided by the present invention adopts in-situ synthesis and then obtains the catalyst by HF etching. The preparation method is simple and can achieve in-situ anchoring of Co and Pd on the nitrogen-doped carbon substrate. The two metals can be evenly dispersed on the nitrogen-doped carbon skeleton substrate and have strong stability, and Pd is not easy to fall off. The present invention is simple to operate, mild in conditions, and has low equipment requirements. It is an environmentally friendly and simple preparation method.
[0029] (3) Compared with the previous bimetallic electrocatalytic materials loaded with Pt nanoparticles and synergistic with Co nitrogen atoms, the Co and Pd bimetallic synergistic electrocatalytic material prepared by the present invention is suitable for electrocatalytic hydrogen evolution research under acidic and alkaline conditions, and exhibits excellent hydrogen evolution effect and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 UiO-66-NH of Examples 1-6 of the present invention 2 、Co 30 / Pd 10 TCPP-UiO-66-NH 2 、Co 20 / Pd 20 TCPP-UiO-66-NH 2 、Co 10 / Pd 30 TCPP-UiO-66-NH 2 、CoTCPP-UiO-66-NH 2 and PdTCPP-UiO-66-NH 2 XRD spectrum of .
[0031] Figure 2 For Examples 7-12 of the present invention, ZrO 2 -NC、Co 30 / Pd 10 -ZrO 2 -NC、Co 20 / Pd 20 -ZrO 2 -NC、Co 10 / Pd 30 -ZrO 2 -NC、Co-ZrO 2 -NC and Pd-ZrO 2 -XRD spectrum of NC.
[0032] Figure 3 NC, Co of Examples 13-18 of the present invention 30 / Pd 10 -NC、Co 20 / Pd 20 -NC、Co 10 / Pd 30 -NC, Co-NC, and Pd-NC XRD spectra.
[0033] Figure 4 UiO-66-NH 2 、Co x / Pd y TCPP-UiO-66-NH 2 、CoTCPP-UiO-66-NH 2 and PdTCPP-UiO-66-NH 2 UV-vis spectrum.
[0034] Figure 5 The present invention Co-NC, Pd-NC, Co 20 / Pd 20 -XPS full spectrum of NC.
[0035] Figure 6 The present invention Co-NC, Pd-NC, Co 20 / Pd 20 XPS spectra of C1s, N 1s, Co 2p and Pd3d of -NC.
[0036] Figure 7 20wt% Pt / C, Co 30 / Pd 10 -NC、Co 20 / Pd 20 -NC、Co 10 / Pd 30 -NC, Pd-NC, Co-NC and NC at 0.5MH 2 SO 4 and LSV polarization curves in 1.0 M KOH electrolyte.
[0037] Figure 8 20wt% Pt / C, Co 30 / Pd 10 -NC、Co 20 / Pd 20 -NC、Co 10 / Pd 30 The catalysts corresponding to -NC, Pd-NC, Co-NC and NC were -2 Overpotential.
[0038] Fig. 9 20wt% Pt / C, Co 30 / Pd 10 -NC、Co 20 / Pd 20-NC、Co 10 / Pd 30 The corresponding Tafel slope curves obtained by analyzing the HER data of -NC, Pd-NC, Co-NC and NC.
[0039] Fig.10 To compare Pt@Co-NC, Co 20 / Pd 20 -NC with 20wt% Pt / C in 0.5MH 2 SO 4 LSV polarization curves in electrolyte. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solutions and advantages of the present invention more clear, the following Figure 1-10 The present invention is further described in detail with reference to the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0041] Additional aspects and advantages of the present invention will be given in part in the following description, and will become apparent from the following description, or learned through the practice of the present invention. It should be understood that the following description is only used to explain the present invention and is not intended to limit the present invention.
[0042] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.
[0043] The phrase "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0044] When dosage, concentration, or other value or parameter is expressed as a range, preferred range, or a range limited by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing a range of "1 to 5", the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0045] In some examples, approximate terms may correspond to the instrumental precision of the measured value. In the present specification and claims, range limits may be combined and / or interchanged. If not otherwise specified, these ranges include all sub-ranges contained therein.
[0046] The indefinite articles "a" and "an" before the elements or components of the present invention have no restrictions on the number of elements or components (i.e. the number of occurrences). Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.
[0047] The terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described in the present invention mean that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the technical features involved in the various embodiments of the present invention can be combined with each other as long as they do not conflict with each other.
[0048] Unless otherwise specified, the raw materials and equipment used in the present invention can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art.
[0049] In some embodiments, a method for preparing a Co / Pd bimetallic catalyst derived from a bimetallic porphyrin-doped MOFs is provided, the preparation method comprising the following steps:
[0050] 1) Add a certain amount of ZrCl 4 、BDC-NH 2 , benzoic acid, CoTCPP and PdTCPP are dissolved in DMF, ultrasonically dissolved and then transferred to a high-pressure reactor for reaction at 100°C-150°C for 16-36h.
[0051] 2) Cooling the solution after the reaction in step 1), recovering the solid product by centrifugation, and repeatedly washing it with ethanol, and then drying it under vacuum at 40 °C to obtain Co / Pd-UiO-66-NH 2 Electrocatalyst.
[0052] 3) Co / Pd-UiO-66-NH 2 Place in a tube furnace and heat under N 2 Calcination under atmosphere to obtain Co / Pd-ZrO 2 -NC.
[0053] 4) Co / Pd-ZrO 2 -NC is added to HF aqueous solution, stirred continuously for 1-5h, washed several times with methanol aqueous solution, and dried under vacuum at 100°C for 2h to obtain Co / Pd-NC, which is a Co / Pd bimetallic catalyst.
[0054] In some embodiments, in the above step 1), the ZrCl 4 、BDC-NH 2 The mass ratio of benzoic acid, CoTCPP and PdTCPP is 9:4.5:100:1-3:1-3, preferably 9:4.5:100:1:1.
[0055] In some embodiments, in the above step 1), ZrCl 4 、BDC-NH 2 The amounts of benzoic acid, CoTCPP and PdTCPP were 180 mg, 90 mg, 2000 mg, 20 mg and 20 mg respectively.
[0056] In some embodiments, in the above step 1), the reaction temperature of the high-pressure reactor is 130° C., and the reaction time is 24 hours.
[0057] In some embodiments, the vacuum drying temperature in the above step 2) is 60°C.
[0058] In some embodiments, in the above step 3), N 2 The calcination conditions in the atmosphere were to heat to 800 °C at a heating rate of 5 °C / min and maintain for 2 h.
[0059] In some embodiments, the HF solution in step 4) is a 15 ml aqueous solution containing 0.1 mol HF, and the stirring time in the HF solution is 2 h.
[0060] In some embodiments, the aqueous solution of methanol in the above step 4) is a mixed solution of methanol and water in a volume ratio of 1:4.
[0061] Some embodiments of the present invention provide a Co / Pd bimetallic catalyst derived from a bimetallic porphyrin-doped MOFs, wherein Co / Pd nanoparticles are fixed and dispersed in a nitrogen-doped carbon skeleton.
[0062] In some embodiments of the present invention, a use of a Co / Pd bimetallic catalyst is provided, and the Co / Pd bimetallic catalyst is used for electrocatalytic hydrogen evolution.
[0063] The following is a further description with reference to specific embodiments.
[0064] Embodiment 1:
[0065] UiO-66-NH 2 The preparation method comprises the following steps:
[0066] (1) Add 180 mg of ZrCl into a beaker. 4 , 90 mg of BDC-NH 2 , 2 g of benzoic acid and 20 mL of DMF;
[0067] (2) After the materials in 1) were dissolved by ultrasonic, the mixture was placed in a 50 mL high pressure reactor and reacted at 130° C. for one day;
[0068] (3) After cooling, the solid product was recovered by centrifugation, washed repeatedly with ethanol, and then dried in vacuum at 60°C to obtain UiO-66-NH 2 .
[0069] Embodiment 2:
[0070] Co 30 / Pd 10 TCPP-UiO-66-NH 2 The synthesis of the electrocatalyst comprises the following steps:
[0071] (1) Add 180 mg of ZrCl into a beaker. 4 , 90 mg of BDC-NH 2 , 2 g of benzoic acid, 30 mg of CoTCPP, 10 mg of PdTCPP and 20 mL of DMF;
[0072] (2) After the materials in 1) were dissolved by ultrasonic, the mixture was placed in a 50 mL high pressure reactor and reacted at 130° C. for one day;
[0073] (3) After cooling, the solid product was recovered by centrifugation, washed repeatedly with ethanol, and then dried in vacuum at 60°C to obtain Co 30 / Pd 10 TCPP-UiO-66-NH 2 .
[0074] Embodiment 3:
[0075] Co 20 / Pd 20 TCPP-UiO-66-NH 2 The synthesis of the electrocatalyst comprises the following steps:
[0076] (1) Add 180 mg of ZrCl into a beaker. 4 , 90 mg of BDC-NH 2 , 2 g of benzoic acid, 20 mg of CoTCPP, 20 mg of PdTCPP and 20 mL of DMF;
[0077] (2) After the materials in 1) were dissolved by ultrasonic, the mixture was placed in a 50 mL high pressure reactor and reacted at 130° C. for one day;
[0078] (3) After cooling, the solid product was recovered by centrifugation, washed repeatedly with ethanol, and then dried in vacuum at 60°C to obtain Co 20 / Pd 20 TCPP-UiO-66-NH 2 .
[0079] Embodiment 4:
[0080] Co 10 / Pd 30 TCPP-UiO-66-NH 2 The synthesis of the electrocatalyst comprises the following steps:
[0081] (1) Add 180 mg of ZrCl into a beaker. 4 , 90 mg of BDC-NH 2 , 2 g of benzoic acid, 10 mg of CoTCPP, 30 mg of PdTCPP and 20 mL of DMF;
[0082] (2) After the materials in 1) were dissolved by ultrasonic, the mixture was placed in a 50 mL high pressure reactor and reacted at 130° C. for one day;
[0083] (3) After cooling, the solid product was recovered by centrifugation, washed repeatedly with ethanol, and then dried in vacuum at 60°C to obtain Co 10 / Pd 30 TCPP-UiO-66-NH 2 .
[0084] Embodiment 5:
[0085] CoTCPP-UiO-66-NH 2 The synthesis of the electrocatalyst comprises the following steps:
[0086] (1) Add 180 mg of ZrCl into a beaker. 4 , 90 mg of BDC-NH 2 , 2 g of benzoic acid and 20 mg of CoTCPP, 20 mL of DMF;
[0087] (2) After the materials in 1) were dissolved by ultrasonic, the mixture was placed in a 50 mL high pressure reactor and reacted at 130° C. for one day;
[0088] (3) After cooling, the solid product was recovered by centrifugation, washed repeatedly with ethanol, and then dried in vacuum at 60°C to obtain CoTCPP-UiO-66-NH 2 .
[0089] Embodiment 6:
[0090] PdTCPP-UiO-66-NH 2 The synthesis of the electrocatalyst comprises the following steps:
[0091] (1) Add 180 mg of ZrCl4 and 90 mg of BDC-NH 2 , 2 g of benzoic acid and 20 mg of PdTCPP, 20 mL of DMF;
[0092] (2) After the materials in 1) were dissolved by ultrasonic, the mixture was placed in a 50 mL high pressure reactor and reacted at 130° C. for one day;
[0093] (3) After cooling, the solid product was recovered by centrifugation, washed repeatedly with ethanol, and then dried in vacuum at 60°C to obtain PdTCPP-UiO-66-NH 2 .
[0094] Embodiment 7:
[0095] ZrO 2 -NC preparation method, comprising the following steps:
[0096] (1) UiO-66-NH 2 Place in a tube furnace and heat under N 2 The sample was heated to 800 °C at a rate of 5 °C / min in an atmosphere and maintained for 2 h.
[0097] (2) Grind the obtained solid to obtain ZrO 2 -NC;
[0098] Embodiment 8:
[0099] Co 30 / Pd 10 -ZrO 2- A method for preparing a NC electrocatalyst comprises the following steps:
[0100] (1) Co 30 / Pd 10 TCPP-UiO-66-NH 2 Place in a tube furnace and heat under N 2 The sample was heated to 800 °C at a rate of 5 °C / min in an atmosphere and maintained for 2 h.
[0101] (2) After grinding the obtained solid, Co 30 / Pd 10 -ZrO 2 -NC;
[0102] Embodiment 9:
[0103] Co 20 / Pd 20 -ZrO 2 - A method for preparing a NC electrocatalyst comprises the following steps:
[0104] (1) Co 20 / Pd 20 TCPP-UiO-66-NH 2 Place in a tube furnace and heat under N 2 The sample was heated to 800 °C at a rate of 5 °C / min in an atmosphere and maintained for 2 h.
[0105] (2) After grinding the obtained solid, Co 20 / Pd 20 -ZrO 2 -NC;
[0106] Embodiment 10:
[0107] Co 10 / Pd 30 -ZrO 2 - A method for preparing a NC electrocatalyst comprises the following steps:
[0108] (1) Co 10 / Pd 30 TCPP-UiO-66-NH 2 Place in a tube furnace and heat under N 2 The sample was heated to 800 °C at a rate of 5 °C / min in an atmosphere and maintained for 2 h.
[0109] (2) After grinding the obtained solid, Co 10 / Pd 30 -ZrO 2 -NC;
[0110] Embodiment 11:
[0111] Co-ZrO 2 - A method for preparing a NC electrocatalyst comprises the following steps:
[0112] (1) CoTCPP-UiO-66-NH 2 Place in a tube furnace and heat under N 2 The sample was heated to 800 °C at a rate of 5 °C / min in an atmosphere and maintained for 2 h.
[0113] (2) Grind the obtained solid to obtain Co-ZrO 2 -NC;
[0114] Embodiment 12:
[0115] Pd-ZrO 2 - A method for preparing a NC electrocatalyst comprises the following steps:
[0116] (1) PdTCPP-UiO-66-NH 2 Place in a tube furnace and heat under N 2 The sample was heated to 800 °C at a rate of 5 °C / min in an atmosphere and maintained for 2 h.
[0117] (2) After grinding the obtained solid, Pd-ZrO 2 -NC;
[0118] Embodiment 13:
[0119] The preparation method of NC electrocatalyst comprises the following steps:
[0120] (1)Place ZrO 2 -NC was added to 15 ml of aqueous solution containing 0.1 mol HF and stirred continuously for 2 h;
[0121] (2) centrifuging the obtained solid and washing it several times with a mixed solution of methanol and water in a ratio of 1:4;
[0122] (3) The solid was dried under vacuum at 100 °C for 2 h to obtain NC.
[0123] Embodiment 14:
[0124] Co 30 / Pd 10 - A method for preparing a NC electrocatalyst comprises the following steps:
[0125] (1) Co 30 / Pd 10 -ZrO 2 -NC was added to 15 ml of aqueous solution containing 0.1 mol HF and stirred continuously for 2 h;
[0126] (2) centrifuging the obtained solid and washing it several times with a mixed solution of methanol and water in a ratio of 1:4;
[0127] (3) The solid was vacuum dried at 100°C for 2 h to obtain Co 30 / Pd 10 -NC.
[0128] Embodiment 15:
[0129] Co 20 / Pd 20 - A method for preparing a NC electrocatalyst comprises the following steps:
[0130] (1) Co 20 / Pd 20 -ZrO 2 -NC was added to 15 ml of aqueous solution containing 0.1 mol HF and stirred continuously for 2 h;
[0131] (2) centrifuging the obtained solid and washing it several times with a mixed solution of methanol and water in a ratio of 1:4;
[0132] (3) The solid was vacuum dried at 100°C for 2 h to obtain Co 20 / Pd 20 -NC.
[0133] Embodiment 16:
[0134] Co 10 / Pd 30 - A method for preparing a NC electrocatalyst comprises the following steps:
[0135] (1) Co 10 / Pd 30 -ZrO 2 -NC was added to 15 ml of aqueous solution containing 0.1 mol HF and stirred continuously for 2 h;
[0136] (2) centrifuging the obtained solid and washing it several times with a mixed solution of methanol and water in a ratio of 1:4;
[0137] (3) The solid was vacuum dried at 100°C for 2 h to obtain Co 10 / Pd 30 -NC.
[0138] Embodiment 17:
[0139] The preparation method of Co-NC electrocatalyst comprises the following steps:
[0140] (1) Co-ZrO 2-NC was added to 15 ml of aqueous solution containing 0.1 mol HF and stirred continuously for 2 h;
[0141] (2) centrifuging the obtained solid and washing it several times with a mixed solution of methanol and water in a ratio of 1:4;
[0142] (3) The solid was dried under vacuum at 100 °C for 2 h to obtain Co-NC.
[0143] Embodiment 18:
[0144] The preparation method of Pd-NC electrocatalyst comprises the following steps:
[0145] (1)Place Pd-ZrO 2 -NC was added to 15 ml of aqueous solution containing 0.1 mol HF and stirred continuously for 2 h;
[0146] (2) centrifuging the obtained solid and washing it several times with a mixed solution of methanol and water in a ratio of 1:4;
[0147] (3) The solid was dried under vacuum at 100 °C for 2 h to obtain Pd-NC.
[0148] Comparative Example 1
[0149] The Pt@Co-NC material prepared in Example 4 of CN116752185A and the Co 20 / Pd 20 -NC catalyst material was used in electrocatalytic hydrogen evolution under the same conditions.
[0150] The electrocatalytic hydrogen evolution experiments of all catalysts of the present invention are as follows:
[0151] The three-electrode test mode was selected, the reference electrode was a saturated calomel electrode, the counter electrode was a carbon rod electrode, the working electrode was a glassy carbon electrode loaded with catalytic material, and the acidic electrolyte was 0.5MH 2 SO 4 , the alkaline electrolyte is 1.0M KOH. The details are as follows:
[0152] Electrocatalytic hydrogen evolution performance test and analysis
[0153] The working electrode was a glassy carbon electrode coated with a catalyst, and the reference electrode and counter electrode were saturated calomel electrode and graphite rod, respectively. Preparation of the working electrode: 1 mg of the catalyst was dispersed in a solution containing EtOH (245 μL), H 2The mixed solution of O (245 μL) and Nafion solution (10 μL) was subjected to ultrasound for about 30 min to fully disperse it. Subsequently, the obtained uniform ink (4 μL) was dropped onto a glassy carbon electrode (3 mm in diameter) and dried naturally to form a film. The mass loading on the electrode was about 0.11 mg cm -2 In addition, a commercial 20 wt % Pt / C electrode was also prepared by the same procedure for comparison.
[0154] In acidic 0.5MH 2 SO 4 The linear sweep voltammetry (LSV) curve was tested in the solution. According to E(vs.RHE)=ESCE+0.241+0.059×pH, the potential value relative to RHE was measured relative to the saturated calomel reference electrode. The frequency range of EIS was 100k to 0.1Hz, and the overpotential was -0.3V. In the potential range where no Faraday process occurs (-0.1~0.3V), the potential was measured at different scan rates (20, 40, 60, 80 and 100mV·s -1 ) were tested by cyclic voltammetry (CV). The electrochemically active surface area was evaluated by double layer capacitance (Cdl). Stability tests were performed by cyclic potential scanning and chronoamperometry (it) (constant current density was 10 mA cm -2 and 100mA·cm -2 )
[0155] LSV was tested in alkaline 1.0 M KOH solution. The potential values relative to RHE were reported according to E(vs.RHE)=EHg / HgO+0.098+0.059×pH and measured relative to a mercuric oxide reference electrode. The frequency range of EIS was 100k to 0.1 Hz, and the overpotential was -1 V. The potential range in which no Faraday process occurs (-0.05 to 0.05 V) was measured at different scan rates (20, 40, 60, 80 and 100 mV·s -1 ) were used for CV test. The electrochemical active surface area was evaluated by double layer capacitance (Cdl). Stability test was performed by cyclic potential scanning method and chronoamperometry (constant current density was 10 mA cm -2 and 100mA·cm -2 ).
[0156] like Figure 1 As shown, the UiO-66-NH obtained in Examples 1-18 2 、Co 30 / Pd 10 TCPP-UiO-66-NH 2 、Co 20 / Pd 20TCPP-UiO-66-NH 2 、Co 10 / Pd 30 TCPP-UiO-66-NH 2 、CoTCPP-UiO-66-NH 2 and PdTCPP-UiO-66-NH 2 The XRD spectrum of Figure 1 As shown, the structural composite rules show that these materials have successfully synthesized MOFs structure.
[0157] like Figure 2 As shown, ZrO 2 -NC、Co 30 / Pd 10 -ZrO 2 -NC、Co 20 / Pd 20 -ZrO 2 -NC、Co 10 / Pd 30 -ZrO 2 -NC、Co-ZrO 2 -NC and Pd-ZrO 2 The XRD spectra of -NC conform to the rules, and the crystal information of these materials after calcination can be seen. The six samples in the figure have a common crystal structure, which is attributed to ZrO 2 The generated (111), (200), (220) and (311) crystal plane information. 2 It is an inert crystal, which is not conducive to electron transfer, but it is easily corroded by acid. 2 The crystals can be completely removed in HF solution.
[0158] like Figure 3 As shown, NC, Co 30 / Pd 10 -NC、Co 20 / Pd 20 -NC、Co 10 / Pd 30 The XRD spectra of -NC, Co-NC, and Pd-NC show a structural composite pattern, which reflects the removal of ZrO by HF. 2 The crystal information of the material after the test is shown in Figure 1. No ZrO was found in the XRD of each sample. 2 The diffraction peaks of the Co / Pd alloy in the sample are clearer. With the change of the Co / Pd component ratio, especially the increase of Co content, the diffraction peaks gradually shift to higher 2θ values. This is because the smaller atomic radius of Co affects the larger lattice spacing of Pd, which fully proves the formation of Co / Pd in the catalyst.
[0159] UiO-66-NH 2 、Co x / Pd y TCPP-UiO-66-NH 2 、CoTCPP-UiO-66-NH 2 and PdTCPP-UiO-66-NH 2 The UV-vis spectrum is as follows Figure 4 As shown, it can be seen that the metal material has a special response in the region, and the absorption trend under visible light can be observed.
[0160] Co-NC, Pd-NC, Co 20 / Pd 20 -NC's XPS full spectrum is as follows Figure 5 As shown, the chemical composition of the material surface can be determined, and the presence of Co, Pd, C, N, and O can be known; Co-NC, Pd-NC, Co 20 / Pd 20 The XPS spectra of C1s, N 1s, Co 2p and Pd 3d of -NC are shown in Figure 6 As shown in the figure, the chemical state and molecular structure can be known from the peak position and peak shape of each element, and the content of the elements in the sample can also be qualitatively analyzed. The XPS full spectra of the three samples are shown in the figure. Figure 5 As shown, according to the XPS results of surface analysis, Co 20 / Pd 20 -NC contains Co, Pd, N, and O elements, among which the content of Co and Pd is close to 1:1. The XPS spectrum of C1s can be deconvoluted into three binding energy peaks, which are attributed to CO, C=N and CC / C=C respectively. The N1s orbital spectra of the three samples have almost the same characteristics, among which various types of doped N can be identified, including pyridinic-N (398.26eV), metal-N (MN, 399.15eV), pyrrolic-N (400.18eV), graphitic-N (401.2eV) and oxidized-N (402.6eV). The formation of MN bonds indicates the existence of a chemical state of coordination between Co / Pd and N. Therefore, Co / Pd can be tightly attached to the carrier, and it is possible to obtain a strong support coordination effect. As shown in the Co 2p diagram, Co 20 / Pd 20 The peak position of Co 2p in -NC is positively shifted relative to that in Co-NC, indicating that the local electron density near Co is reduced and the Co element is 20 / Pd 20 The XPS spectra of Pd 3d orbitals show that Co 20 / Pd 20The Pd 3d peak of -NC shifts to the direction of lower binding energy, which verifies the Co atom in Co 20 / Pd 20 The XPS results demonstrate that there is a synergistic but asymmetric electron distribution between the two metals, which optimizes the Co 20 / Pd 20 The electronic structure of -NC is conducive to electrocatalytic hydrogen evolution.
[0161] 20%wt%Pt / C,Co 30 / Pd 10 -NC、Co 20 / Pd 20 -NC、Co 10 / Pd 30 -NC, Pd-NC, Co-NC and NC at 0.5MH 2 SO 4 The LSV polarization curves in 1.0M KOH electrolyte are shown in Figure 7 As shown in the figure, the hydrogen evolution performance of each catalyst can be seen, among which Co has the best HER performance. 20 / Pd 20 -NC catalyst; the corresponding catalyst at 10 mA cm -2 Overpotential Figure 8 As shown, Co 20 / Pd 20 -NC catalyst has an acid-base transition point of 23mv and 52mv, which is comparable to the effect of commercial Pt / C catalyst;
[0162] The corresponding Tafel slope curve obtained from the HER data analysis is as follows Fig. 9 As shown in Figure 1, the Tafel curve is the slope of the linear relationship between the fitted current density and the overpotential. A lower Tafel slope means faster reaction kinetics, indicating that the catalyst can reach the desired current at a lower overpotential. It is a useful tool for evaluating the HER performance of catalysts. Compared with the Tafel slopes of single metal Co-NC, Pd-NC catalysts and commercial Pt / C catalysts, Co 20 / Pd 20 The Tafel slope of -NC is even lower, only 34.7 mV·dec in acid / base solution. -1 and 55.4mV·dec -1 , which means it has a faster reaction kinetics. It can be seen that the Co / Pd bimetallic structure can greatly improve the HER activity, where Co 20 / Pd 20 -NC ratio is optimal and the catalytic hydrogen evolution effect is best.
[0163] Fig.10 For Pt@Co-NC, Co 20 / Pd 20 -NC with 20wt% Pt / C in 0.5MH 2 SO 4 The LSV polarization curve in the electrolyte shows that at a current density of 10 mA cm -2 Compared with the standard hydrogen electrode, Co 20 / Pd 20 -NC catalyst has a better overpotential than Pt@Co-NC, indicating that the catalyst Co 20 Pd 20 -NC performs better than Pt@Co-NC.
[0164] In summary, the present invention proposes a "pre-constrained bimetallic" strategy, using CoTCPP and PdTCPP with unique porphyrin ring structures as structure-directing agents, in-situ integrated synthesis of CoTCPP and PdTCPP-doped MOFs-derived Co / Pd bimetallic catalysts, and using metal organic framework materials formed by metal ligands to achieve spatial isolation of the bimetallics. The doped MOFs are pyrolyzed at high temperature, and the metal nanoparticles Co / Pd are firmly anchored on the nitrogen-doped carbon skeleton substrate to form a tight interface connection. In addition, the nitrogen-doped carbon skeleton is used to achieve uniform distribution of Co / Pd metal nanoparticles, promote the electronic synergy between non-precious metal Co and precious metal Pd, thereby improving the hydrogen evolution catalytic performance of the Co / Pd bimetallic catalyst. The Co / Pd bimetallic catalyst obtained by the preparation method of the present invention has excellent electrocatalytic hydrogen evolution performance in the field of electrocatalytic hydrogen evolution and has important application value.
[0165] It is easy for those skilled in the art to understand that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a Co / Pd bimetallic catalyst derived from bimetallic porphyrin-doped MOFs, characterized in that: The preparation method comprises the following steps: 1) Dissolve a certain amount of ZrCl4, BDC-NH2, benzoic acid, CoTCPP, and PdTCPP in DMF, dissolve them by ultrasonication, and then transfer them to a high-pressure reactor for reaction at 100℃-150℃ for 16-36h; 2) cooling the solution after the reaction in step 1), recovering the solid product by centrifugation, repeatedly washing it with ethanol, and then drying it in a vacuum to obtain a Co / Pd-UiO-66-NH2 electrocatalyst; 3) Place Co / Pd-UiO-66-NH2 into a tube furnace and calcine under N2 atmosphere to obtain Co / Pd-ZrO2-NC; 4) Add Co / Pd-ZrO2-NC to HF aqueous solution, stir continuously for 1-5h, wash with methanol aqueous solution several times, and dry under vacuum at 100℃ for 2h to obtain Co / Pd-NC, which is Co / Pd bimetallic catalyst; In the step 1), the mass ratio of ZrCl4, BDC-NH2, benzoic acid, CoTCPP and PdTCPP is 9:4.5:100:1-3:1-3.
2. The method for preparing a Co / Pd bimetallic catalyst derived from bimetallic porphyrin-doped MOFs according to claim 1, characterized in that: In the step 1), the amounts of ZrCl4, BDC-NH2, benzoic acid, CoTCPP and PdTCPP are 180 mg, 90 mg, 2000 mg, 20 mg and 20 mg respectively.
3. The method for preparing a Co / Pd bimetallic catalyst derived from bimetallic porphyrin-doped MOFs according to claim 1, characterized in that: In the step 1), the reaction temperature of the high-pressure reactor is 130° C., and the reaction time is 24 hours.
4. A method for preparing a Co / Pd bimetallic catalyst derived from a bimetallic porphyrin-doped MOFs according to any one of claims 1 to 3, characterized in that: The vacuum drying temperature in step 2) is 60°C.
5. A method for preparing a Co / Pd bimetallic catalyst derived from a bimetallic porphyrin-doped MOFs according to any one of claims 1 to 3, characterized in that: The conditions for calcination under N2 atmosphere in step 3) are heating to 800°C at a heating rate of 5°C / min and maintaining for 2h.
6. A method for preparing a Co / Pd bimetallic catalyst derived from bimetallic porphyrin-doped MOFs according to any one of claims 1 to 3, characterized in that: In step 4), the HF solution is a 15 ml aqueous solution containing 0.1 mol HF, and the stirring time in the HF solution is 2 h.
7. A method for preparing a Co / Pd bimetallic catalyst derived from bimetallic porphyrin-doped MOFs according to any one of claims 1 to 3, characterized in that: The aqueous solution of methanol in step 4) is a mixed solution of methanol and water in a volume ratio of 1:
4.
8. A Co / Pd bimetallic catalyst derived from a bimetallic porphyrin-doped MOFs prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The Co / Pd nanoparticles are fixed and dispersed in the nitrogen-doped carbon framework.
9. Use of the Co / Pd bimetallic catalyst according to claim 8, characterized in that: Co / Pd bimetallic catalysts were used for electrocatalytic hydrogen evolution.
Citation Information
Patent Citations
Synthesis and application of Pt nanoparticle synergistic Co monatomic bimetallic electro-catalytic material
CN116752185A
Preparation and application of porous composite material electrocatalyst based on bimetallic macrocyclic compound
CN111146457A
Preparation method and application of composite electrocatalyst for reducing CO2
CN113529108A
Synthesis and application of Co monatomic modified bimetallic Pt-based electro-catalytic material
CN118756210A